Examining healthcare professionals' beliefs and actions regarding the physical health of people with schizophrenia - Alexandra Berry; Richard J. Drake; Alison R. Yung (BMC, 2020)
Abstract Background People with schizophrenia have a higher premature mortality risk compared with the general population mainly due to cardiovascular disease (CVD). Despite this, people with schizophrenia are less likely to access physical health services or have their physical health investigated and monitored. Aims To examine the beliefs and actions of mental health professionals regarding the physical health of people with schizophrenia. Method Two hundred and fifty-five healthcare professionals who support people with schizophrenia within Greater Manchester Mental Health NHS Foundation Trust (GMMH), United Kingdom and Pennine Care NHS Foundation Trust (PCFT), United Kingdom took part. Beliefs and actions were assessed using a self-administered questionnaire, which was constructed around two primary domains (1) CVD risk factors; and (2) physical health interventions. Descriptive statistics were reported and responses between different healthcare professional groups were compared. Results The overwhelming majority of participants were aware of established CVD risk factors with 98% identifying family history of CVD, 98% for smoking and 96% for high blood pressure. Most participants believed nearly all healthcare professionals were responsible for monitoring the physical health of people with schizophrenia, regardless of job speciality. There were 67% of participants who reported delivering an intervention to improve sedentary behaviour for people with schizophrenia. However, awareness of government and NHS recommended lifestyle interventions were low. Conclusions This study found good knowledge regarding many established CVD risk factors but little clarity regarding who is responsible for monitoring the physical health of people with schizophrenia and how often brief lifestyle interventions are being implemented.